Revolutionary Movements in the 20th Century: A Comparative Analysis in USA - Williams, Robert (International Journal of History Research, 2024)
Purpose: The aim of the study was to investigate revolutionary movements in the 20th century: a comparative analysis. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Revolutionary movements in the 20th century, such as the Russian Revolution, the Chinese Communist Revolution, and the Cuban Revolution, each aimed to overthrow existing regimes and establish socialist states. Led by figures like Lenin, Mao Zedong, and Fidel Castro, these movements varied in their approaches and outcomes, yet all significantly impacted global politics and ideologies. Unique Contribution to Theory, Practice and Policy: Dependency theory, social movement theory & world-systems theory may be used to anchor future studies on revolutionary movements in the 20th century: a comparative analysis. Recognize the agency of grassroots movements and civil society organizations in driving revolutionary change, and support initiatives that empower marginalized communities to articulate their grievances and pursue social justice. Prioritize policies that address the underlying socio-economic inequalities, political repression, and cultural marginalization that often fuel revolutionary movements, focusing on poverty reduction, social welfare, and inclusive development.